Pediatric severe sepsis: epidemiology and risk factors associated with acute kidney injury - Li, Haibo; Zhang, Ying; Zhu, Hongyan; Yu, Ran; Zhou, Qi; Song, Jiannan; Wu, Jiannan; Ma, Wanli; Hu, Zhanfei; Wang, Jian; Yu, Xuegao; Zhang, Hongyu (Frontiers in Pediatrics, 2026)
BackgroundPediatric severe sepsis (PSS) is one of the leading causes of morbidity and mortality in children, incurring substantial social costs. Acute kidney injury (AKI) plays a critical role in determining PSS severity and prognosis. However, existing literature provides limited data regarding the risk factors associated with AKI in pediatric sepsis patients and the impact of AKI on hospital outcomes for these patients. This study aimed to analyze the temporal trends in incidence and outcomes of AKI among hospitalized PSS patients from 2010 to 2019, and identify associated risk factors; and assess the impact of AKI on in-hospital mortality and healthcare resource utilization.MethodsThis study utilized the nationally representative National Inpatient Sample (NIS) database of the United States to conduct a retrospective analysis. All children aged 0 (infants) to 18 years who were diagnosed with severe sepsis between 2010 and 2019 were included. Patients were grouped by AKI status, and in-hospital mortality and medical resource utilization (length of stay and inflation-adjusted costs) were compared. Multivariate regression identified AKI risk factors.ResultsThe incidence rate of AKI among hospitalized PSS patients increased from 2.7% in 2010 to 8.0% in 2019. However, in-hospital mortality declined from 32.40% to 17.90% over the same period. The incidence of AKI was significantly higher in patients with comorbidities. Studies have shown that hospitalizations associated with AKI have a higher likelihood of involving infection sites and a variety of pathogenic flora.ConclusionWhile the incidence of AKI increased from 2010 to 2019, associated mortality decreased. This likely reflects advancements in critical care that are improving survival, even as more cases are recognized. AKI, affecting 5% of PSS patients, remained a potent marker of severity, was associated with a sevenfold increased risk of mortality and driven by identifiable risk factors like specific comorbidities and infections. Enhanced early identification of at-risk children is crucial to further improve outcomes.